PENGEMBANGAN PROTOTIPE ALAT UJI PERMEABILITAS BETON BERPORI UNTUK MENENTUKAN KOEFISIEN PERMEABILITAS - Rabinah, Aiun Hayatu; Jamal Mahbub; Suparman; Lilik Satriyadi; Parhadi; Bimawijaya Laia (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2025)
The increasing growth of infrastructure and building development has led to a reduction in land surface cover. The lack of surface cover significantly impacts the environment, such as causing severe flooding. To address water-related issues, one approach is to manage runoff at its source through Low Impact Development (LID) strategies, such as permeable pavements. One method used to infiltrate water is porous concrete. Key parameters of porous concrete include strength, water-cement ratio, porosity, and permeability coefficient. The permeability coefficient of porous concrete is obtained through permeability testing. Laboratory permeability tests are more commonly used than field-testing. Therefore, it is important to have a dedicated tool for testing the permeability of porous concrete. The first stage involves the development and testing of a prototype, which includes prototype design, material survey, material procurement, equipment preparation, prototype construction, and testing. The prototype development refers to the ACI 522R-10 standard. The results of the prototype testing are analyzed using Darcy’s law to determine the permeability coefficient and analyze the flow characteristics. Based on the research findings, the permeability test prototype for porous concrete can be used as a testing tool for porous concrete permeability both in laboratory and field settings. The prototype exhibits laminar flow, thus allowing Darcy’s law to be applied for evaluating hydraulic conductivity.